Study on the Synthesis and Photocatalytic Perfomance of Tube shaped Activated Carbon -TiO2 Composite Materials - Wu, Zhifu (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Titanium dioxide semiconductor material is one of the earliest photocatalysts with stable and reliable properties, but its quantum efficiency is relatively low. In order to improve the photocatalytic performance of titanium dioxide, the activated carbon tubular-titanium dioxide composite photocatalytic material was synthesized by sol-gel method with n-butyl titanate and activated carbon as main raw materials in the system of isopropyl alcohol and glacial acetic acid. X-ray diffraction (XRD), scanning electron microscope (SEM) and nitrogen adsorption were used to characterize the phase, particle size and adsorption performance of the photocatalyst. The photocatalytic performance of the synthesized material was tested by using rhodamine B, a simulated pollutant. The results show that rhodamine B decomposition rate can reach 100% under UV irradiation for 140 minutes. The conclusion is that the photocatalytic performance of the activated carbon tube interspersed with titanium dioxide composite was significantly improved.